Long-distance trade in al-‘Ūla from the Mamluk period to the 20th century AD: technological, morphological and compositional study of glass bangles collected in al-‘Ūla oasis (Hejaz, Saudi Arabia) - Furstos, Cassandra; Pellegrino, Maria Paola; Leschallier de Lisle , Anne; Kanhoush, Yasmin; Charbonnier, Julien (Proceedings of the Seminar for Arabian Studies, 2023)
Over four hundred fragmentary coloured glass bangles have been so far collected in the al-‘Ūla oasis during the archaeological survey carried out within the framework of the ongoing al-‘Ūla Cultural Oasis Project (UCOP) led by Archaïos, funded and steered by the French Agency for al-‘Ūla Development (AFALULA) on behalf of the Royal Commission for al-‘Ūla (RCU). A technological and morphological study has enabled the establishment of a typology and a relative chronology of the various glass jewellery productions in al-‘Ūla. Several criteria allow us to isolate different glass productions and to draw connections between al-‘Ūla’s assemblage, still unpublished, and other glass bangles corpus located in the neighbouring regions, mainly in Palestine and Egypt, and farther afield, in the Indian Ocean and in Bohemia. Spatial distribution and compositional analysis (LA-ICP-MS) of the well-dated types of glass bangles thus provide evidence to both the evolution of al-‘Ūla oasis and its role within the trade networks and the Hajj route from the fourteenth to the twentieth centuries AD.